2016
DOI: 10.1099/mic.0.000341
|View full text |Cite
|
Sign up to set email alerts
|

The soil microbiome at the Gi-FACE experiment responds to a moisture gradient but not to CO2 enrichment

Abstract: The soil bacterial community at the Giessen free-air CO 2 enrichment (Gi-FACE) experiment was analysed by tag sequencing of the 16S rRNA gene. No substantial effects of CO 2 levels on bacterial community composition were detected. However, the soil moisture gradient at Gi-FACE had a significant effect on bacterial community composition. Different groups within the Acidobacteria and Verrucomicrobia phyla were affected differently by soil moisture content. These results suggest that modest increases in atmospher… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
8
3

Year Published

2017
2017
2024
2024

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 15 publications
(13 citation statements)
references
References 72 publications
2
8
3
Order By: Relevance
“…Nonetheless, trac's taxonomic groupings provide meaningful information about the taxonomic structure of soil microbiota along moisture gradients. For example, the model supports the positive association between Proteobacteria and moisture, as previously observed in a study along a vegetation gradient on the Loess Plateau in China (Zeng et al, 2016), and the negative effect of moisture on the phylum Verrucomicrobia and the positive effect on Deltaproteobacteria in the Giessen free-air CO2 enrichment (Gi-FACE) experiment (de Menezes et al, 2016). The Gi-FACE study, however, also reported several relationships between the microbiome and the soil moisture that are incongruent with our model, including the role of Acidobacteria.…”
Section: Predicting Central Park Soil Properties From Microbial Commusupporting
confidence: 84%
“…Nonetheless, trac's taxonomic groupings provide meaningful information about the taxonomic structure of soil microbiota along moisture gradients. For example, the model supports the positive association between Proteobacteria and moisture, as previously observed in a study along a vegetation gradient on the Loess Plateau in China (Zeng et al, 2016), and the negative effect of moisture on the phylum Verrucomicrobia and the positive effect on Deltaproteobacteria in the Giessen free-air CO2 enrichment (Gi-FACE) experiment (de Menezes et al, 2016). The Gi-FACE study, however, also reported several relationships between the microbiome and the soil moisture that are incongruent with our model, including the role of Acidobacteria.…”
Section: Predicting Central Park Soil Properties From Microbial Commusupporting
confidence: 84%
“…A lack of response of microbial communities against long-term exposure to e CO 2 was reported previously (Haase et al, 2008 ; Nelson et al, 2010 ; Marhan et al, 2011 ; Regan et al, 2011 ; Pujol Pereira et al, 2013 ; Dunbar et al, 2014 ). In addition, de Menezes et al ( 2016 ) showed for GiFACE that e CO 2 exerted no substantial effects on the composition of the overall soil bacterial community. Likewise, microbial communities involved in denitrification, ammonia oxidation, and DNRA remained unaffected by e CO 2 in other studies (Deiglmayr et al, 2004 ; Haase et al, 2008 ; Marhan et al, 2011 ; Pujol Pereira et al, 2013 ).…”
Section: Discussionmentioning
confidence: 99%
“…A previous study found differences in the water level in the deeper soil layers at GiFACE in the order: E1/A1 < E3/A3 < E2/A2 (Lenhart, 2008 ). de Menezes et al ( 2016 ) attributed differences in bacterial community composition at GiFACE to the soil moisture gradient. Long-term differences in the water level of the deeper soil layers probably determined the differences in pH and the concentration of C- and N-compounds observed in the top soil layer (0–7.5 cm) of the sets.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…However, it should be noted that elevated CO 2 level in most of the FACE study sites was >500 ppm (Drissner et al, ; Ebersberger et al, ; Hagedorn et al, ; Xu et al, ), the highest CO 2 concentration applied in this study. A recent study at Giessen free‐air CO 2 enrichment (Gi‐FACE) facility in Germany, which examined grassland communities exposed to ambient (400 ppm) and moderate (480 ppm) CO 2 levels (de Menezes, Müller, Clipson, & Doyle, ), also demonstrated negligible effect of CO 2 on bacterial communities. In agreement with our findings, they showed more pronounced effects of soil moisture than CO 2 enrichment on bacterial community structure and diversity.…”
Section: Discussionmentioning
confidence: 99%